A new treatment of alloying effects on migrating interfaces in Fe-X alloys. (15th March 2019) - Zhang, Cong-Yu; Chen, Hao; Zhu, Jia-Ning; Liu, Wen-Bo; Liu, Geng; Zhang, Chi; Yang, Zhi-Gang
Abstract: The steady-state assumption in the classical solute drag (SD) models is not always valid in treating the complex interaction between alloying elements and migrating interfaces (grain/phase boundaries) in steels. In this study, a general treatment based on phase-field theory is proposed to capture the SD effects of alloying elements without the steady state assumption, while it reduces to the SD models under steady-state assumption. This new treatment can predict the interaction between migrating interfaces and alloying elements with strong segregation tendencies, which cannot be captured by the classical SD models. Graphical abstract: Unlabelled Image